Der europäische Beobachter außereuropäischer Kulturen (Duncker & Humblot, 2025)
The ZHF provides a forum for research on the history of premodern Europe. Its concept is based on the idea of viewing the periods of the Late Middle Ages and the Early Modern era as a structural unit that transcends the caesura around 1500. In addition to scholarly articles, the ZHF regularly features current research reports and an extensive review section. A thematic supplement is published twice a year.